2017
DOI: 10.1039/c6nr09270e
|View full text |Cite|
|
Sign up to set email alerts
|

Soft electrothermal actuators using silver nanowire heaters

Abstract: Low-voltage and extremely flexible electrothermal bimorph actuators were fabricated in a simple, efficient and scalable process. The bimorph actuators were made of flexible silver nanowire (AgNW) based heaters, which exhibited a fast heating rate of 18 °C s and stable heating performance with large bending. The actuators offered the largest bending angle (720°) or curvature (2.6 cm) at a very low actuation voltage (0.2 V sq or 4.5 V) among all types of bimorph actuators that have been reported to date. The act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
143
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 155 publications
(144 citation statements)
references
References 64 publications
1
143
0
Order By: Relevance
“…For instance, actuators or stimulators may be incorporated to achieve interactive devices that can interact with human body, another device or the environment. [22,37,170,187] Drug-delivery platforms can be integrated to enable therapeutic treatments in response to the information collected by the wearable sensors. [188][189][190] Energy scavengers could negate the need for frequently charging batteries or completely replace the batteries.…”
Section: Integrated Wearable Systemsmentioning
confidence: 99%
“…For instance, actuators or stimulators may be incorporated to achieve interactive devices that can interact with human body, another device or the environment. [22,37,170,187] Drug-delivery platforms can be integrated to enable therapeutic treatments in response to the information collected by the wearable sensors. [188][189][190] Energy scavengers could negate the need for frequently charging batteries or completely replace the batteries.…”
Section: Integrated Wearable Systemsmentioning
confidence: 99%
“…Recently, a promising Ag nanowire (Ag NW)-based ETA with a very low driving voltage (<5 V) has developed. [23] However, the Ag NW embedded multilayers exhibit a weak bonding strength (0.72 N cm −1 ) [33] between actuator multilayers, and can therefore be delaminated during the generation of mechanical stress at the interface. Thus, further development to achieve low driving voltage and robust bonding simultaneously is needed.…”
Section: Wwwadvmattechnoldementioning
confidence: 99%
“…[21,22] Unfortunately, this approach requires the use of highly aligned nanomaterials and complex electrical paths, which limits the material scope and increases the driving voltage. Alternatively, the shape diversity problem has been solved by attachment of stiff materials [23] on some parts or by making use of the anisotropic expansion of an actuation material. [24,25] However, the design diversity needs to be increased further, as expansion directions cannot be locally controlled with a single substrate geometry, and the attachment of stiff materials does not allow for continuous shape actuation.…”
mentioning
confidence: 99%
“…Third, choose proper elastic substrate materials with greater thermal expansion and excellent flexibility such as polyimide (PI), PDMS and so on. Among these polymers, PDMS has been widely used as the substrate in recent years in order to form larger coefficient of thermal expansion difference with the heating layer to increase the deformation further, such as the structure of SACNS/PDMS, sG/PDMS, CNT/PDMS, rGO/PDMS, PI/AgNW/PDMS, CNT(BP)/PDMS, and many others. In addition, studies have shown that decreasing the thickness of the actuator in an appropriate range can help achieving a shorter response time greatly due to the short heat transfer path as well as enlarging the deformation in a degree.…”
Section: Thermoelectric Coupling Devicementioning
confidence: 99%